PENINGKATAN KEMAMPUAN KOGNITIF ANAK USIA DINI DALAM MENGENAL ANGKA 1-10 MELALUI MEDIA BAHAN ALAM DI RAUDHATUL ATHFAL AL GHAZALI MEDAN TP. 2020-2021 - Hasnah Siahaan, Nurul Hafizah, Etika Ratna, Khadijah Santi (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2020)
ABSTRAK: In the world of education today, especially in early childhood education institutions, there is rapid progress and competition in improving the quality of early childhood education institutions. Therefore, each educational institution implements the learning process in various ways in using the right teaching methods and learning media that are appropriate and easily understood by students so that the material taught is achieved. Not a few educational institutions delivered by their educators did not understand the appropriate learning media on the material they were teaching. Therefore, the purpose of this study is to determine the appropriate media in recognizing numbers, especially numbers 1 to 10. The method of this research is classroom action research. The results of the study are the learning media used in recognizing numbers 1 to 10 using media from natural materials and have increased according to the development of the results of the cycle, namely in the first cycle the criteria developed according to expectations and in the second cycle the results of the criteria developed very well.Keyword:  Cognitive, Early Childhood.